2018
DOI: 10.1111/jpr.12241
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pink/Blue Clothing on Implicit and Explicit Gender‐Related Self‐Cognition and Attitudes Among Men

Abstract: In many cultures worldwide, one stereotype emerges: Pink is associated with girls and blue is associated with boys. Based on the enclothed cognition theory, the present study examined the effects of men's pink clothing on gender‐related self‐cognition and sex‐role attitudes. Male Japanese participants wore either a pink or blue coat and completed a gender stereotype Implicit Association Test, a self‐rating scale, and gender attitude scales (a measure of egalitarian sex‐role attitude and the Ambivalent Sexism I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…In Japan, reddish and bluish colors are often used to represent female and male gender symbols, respectively, in social and public service systems. For instance, the symbol of the female lavatory is often colored in red or pink while that of the male lavatory is often colored in blue or green 6 – 8 . It is common for reddish colors to be widely used in clothes, cosmetics, and activities for girls and women while blue/green colors are more frequently used in male clothes and behaviors/interests in the modern daily life.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, reddish and bluish colors are often used to represent female and male gender symbols, respectively, in social and public service systems. For instance, the symbol of the female lavatory is often colored in red or pink while that of the male lavatory is often colored in blue or green 6 – 8 . It is common for reddish colors to be widely used in clothes, cosmetics, and activities for girls and women while blue/green colors are more frequently used in male clothes and behaviors/interests in the modern daily life.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, women wear red more often than do men (Frank, 1990). Signals of the female body in red/pink and male body in blue/green have been widely used in public services in Japan (e.g., gender signages for washrooms; Ishii et al, 2019;Kitagami et al, 2009). Thus, people might learn redfemale associations through the mere exposure to co-occurrences of red and feminine traits, and applied them in body-sex processing and behaviors (Cunningham & Macrae, 2011;Yeung & Wong, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…With the developmental in uence of these gender-color related social and cognitive processes, both children and adults show gender differences in color preference, possibly leading to female preference for pink/reddish colors and male preference for blue/green colors ( In Japan, reddish and bluish colors are often used to represent female and male gender symbols in social and public service systems. For instance, the symbol of the female lavatory is often colored red or pink, whereas that of the male lavatory is often colored blue or green (Ishii et al, 2019;Kitagami et al, 2009Kitagami et al, , 2010. A study of Japanese color preference reported a liking for reddish colors in females and bluish colors in males (Saito, 1996).…”
Section: Introductionmentioning
confidence: 99%